REQUIREMENTS TO PUBLISH - INVESTICGA, Revista
The Journal of Research in Administrative Management and Information Sciences INVESTICGA is an online annual publication created by the Administrative Management Center of the Capital District Regional, for the educational community (apprentices, instructors, administrative personnel, businessmen and external people) to have a space to publish articles of reflection,research and revision, product of the projects carried out that generate new knowledge and contribute to a practical development.